An analysis of the effect of real gross domestic product on unemployment in Nigeria: (an ARDL- approach) - Buba, Saad; Ishak, Suryati (International Institute for Science, Technology & Education, 2014)
This study examined the effect of real Gross Domestic Product (GDP) on unemployment in Nigeria. Unemployment is a major problem in Nigeria, even with the recent growth rate of 7% the country is recording, unemployment is still on the increase. The study considers the period 1977 to 2011 to analyse the long run and shot run relationship between real gross domestic product and unemployment in Nigeria, with unemployment as a dependent variable. Besides the main variables for this study, other control variables particularly inflation was included in the model. The study has used Autoregressive Distributed Lag (ARDL) Model to test for ARDL- bound co-integration test, the long run and the Error Correction Model (ECM). The co-integration bound test results showed that the variables are co-integrated at 5% level. The results revealed a positive relationship between unemployment and real GDP in Nigeria both in the short run and in the long run. The study concludes that real GDP growth causes unemployment in Nigeria and suggests that Nigeria as a country should reduce the over reliance on petroleum sector as a source of revenue and give more emphasis on other sectors, especially agricultural sector in order to provide more job opportunities to the Nigerian citizens. Also, the government should use the huge revenue it derives from the oil sector to develop other sectors like iron and steel sector, agriculture and so on. The government should also provide environment that will attract capital and investment, the government does not necessary create jobs but does aid the private sector in making job creation possible and imminent.